2006
DOI: 10.1111/j.1745-4514.2006.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Chemical Properties of Ikivunde and Inyange, Two Traditionally Processed Burundian Cassava Flours

Abstract: Ikivunde and Inyange are traditionally processed cassava flours that are widely consumed in Burundi. Functional and chemical properties were measured at fermentation periods of 0, 24, 48, 72, 96 and120 h. Yield, bulk density, dispersibility, crude fiber and pasting temperature (PT) increased as the fermentation time increased for both products. In addition, decreases in pH, starch, cyanide, peak viscosity (PV), hot paste viscosity, cold paste viscosity and water retention capacity were also observed as the fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The dispersions were stirred with a glass rod and kept for 30 min at ambient temperature (28 ± 2 °C), followed by centrifugation at 3000 g for 10 min. The volume of the supernatant was recorded, and the oil retained by the protein isolate was expressed as mL of oil or water per g of protein …”
Section: Methodsmentioning
confidence: 99%
“…The dispersions were stirred with a glass rod and kept for 30 min at ambient temperature (28 ± 2 °C), followed by centrifugation at 3000 g for 10 min. The volume of the supernatant was recorded, and the oil retained by the protein isolate was expressed as mL of oil or water per g of protein …”
Section: Methodsmentioning
confidence: 99%
“…The highest value was observed in native acha flour and cookie samples while least value was observed in sample fermented for 72 h. The decrease observed in the loose and tapped bulk density might possibly result from increased particle breakdown of the fibrous materials during fermentation (Olapade et al, 2014). According to Nzigamasabo and Hui (2006), pectinolytic and cellulotic enzymes are elaborated by fermenting microorganisms and aid in the breakdown of cell membranes. The formation of carbon dioxide gas during fermentation, which causes the bubbles to grow in size and increase in volume may also be the reason of the decrease in bulk density of flour samples with longer fermentation durations (Elmehdi et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Nutrient losses may vary depending on the type of technology used, from completely traditional and manual to semi‐mechanised. Aloys & Zhou (2005) indicated that longer fermentation of raw cassava is associated with several traits of the processed gari: higher yield, higher density, higher dispersibility, higher crude fibre, and higher pasting temperature, but lower pH, starch, cyanide content, peak viscosity, paste viscosity and water retention of the gari. About 80% of the dry matter in cassava root consists of carbohydrates, including starch in the majority, fibre and sugars (Kim et al ., 1995; Huang et al ., 2007; Goddard et al ., 2015).…”
Section: Processing Methods Product Characterisation and Relationshimentioning
confidence: 99%